Corporate boards - Sila, Vathunyoo (The University of Edinburgh, 2015)
This thesis comprises three empirical studies. These studies can be read as though they are independent. However, all three of them revolve around investigating whether and how characteristics of directors can affect firm-level outcomes. The first study – “Does gender diversity affect firm equity risk?” – systematically investigates whether gender diversity in the boardroom influences firm equity risk. To identify the causal effect of gender on risk, I employ a dynamic model which allows for the possibilities that risk can influence the gender of appointed directors and that both director gender and risk can be influenced by other unobserved firm-level factors. The overall results in this study do not support the view that female boardroom representation influences equity risk. I also show that findings of a negative relationship between the two variables are spurious and driven by unobserved between-firm heterogeneous factors. The second study – “Spillover effects of women on boards” – introduces an alternative way of looking at boardroom gender diversity. The definition of boardroom gender diversity is broadened to include female directors who do not sit on the board but are connected to the board through male directors or “external” female influence. This is in addition to the “internal” influence of female directors inside the board. I find that when both external and internal influences of female directors are considered, there is evidence supporting a link between gender diversity and firm risk and that a plausible channel by which gender affects risk is through more effective monitoring. Male directors are less likely to exhibit absenteeism when they are exposed to both external and internal female influence. CEO turnover sensitivity increases with the proportion of male directors who are externally connected to women, when there is at least one female director inside the board. Risk also increases with the proportion of these connected men when they work on a board with at least one woman. The findings suggests that female directors can exert influence on firm-level outcomes despite their minority status in the boardroom. The third study – “Independent director reputation incentives and stock price informativeness” – examines whether the reputation incentives of independent directors increase the incorporation of firm-specific information into stock prices. I find that the proportion of directors who deem their directorships to be more important based on firm market capitalization is associated with higher firm-specific information content in stock prices. This is consistent with the argument that boards that are incentivized to protect their reputation can deter managers from withholding information. I find this relation to be stronger when other external monitoring mechanisms are weak and when there is uncertainty regarding the future prospects of the firm. I also find evidence that a channel by which directors can influence stock price informativeness is through voluntary disclosure. Additionally, the presence of directors with high reputation incentives is negatively associated with stock price crash.
Essays on corporate boards
Keywords: corporate governance; board of directors